Global Longitudinal Strain and Post Systolic Index as Related To E/e, Ratio in Male Patients with Hypertension (Texas Journal of Medical Science, 2022)
High incidence of morbidity and mortality is associated with systemic hypertension because to its negative effects on a variety of systems, particularly the cardiovascular system. Diastolic dysfunction is a prominent component of this illness, and despite growing recognition of its importance, it is still underappreciated due to its challenging identification and lack of effective treatments. Despite the presence of normal left ventricular (LV) systolic indices, estimate of LV systolic function using strain concepts has recently been shown to be able to differentiate patients with systolic dysfunction. There is little evidence linking hidden myocardial alterations to diastolic dysfunction. The goal of this study is to determine occult left ventricle systolic dysfunction and its relationship to diastolic dysfunction in non-complicated hypertensive patients under the age of 40. Methods: This study included a total of 100 young male volunteers. The research will run from January until April 2020. A sample was taken from the Al-Furat teaching hospital's consulting room.. Hypertensive patients are grouped as group A (E/e,